IN VITRO ACCUMULATION OF CADMIUM CHLORIDE IN PAPAYA SEEDLING AND ITS IMPACT ON PLANT PROTEIN - Anju, Meshram; Sanskriti, Gautam; Sameer Suresh, Bhagyawant; Nidhi, Srivastava (International Journal of Ayurveda and Pharma Research, 2015)
Background: Carica papaya has wide range of applications in traditional medicine. It has high nutritional content and various medical applications. Objectives: In the present study, changes have been observed at the morphological, biochemical, antioxidation and protein level in Carica papaya L variety Pusa Dwarf by accumulation of cadmium chloride in vitro. Material and methods: Plants were treated with different concentrations (20ppm, 40ppm, 60ppm and 80ppm) of cadmium chloride, and examined changes in growth and protectively induced oxidative stress in relation to heavy metal in three weeks old seedlings. Protein profiling by SDS-PAGE was done to study the influence of severe heavy metal stress in Carica papaya L. variety Pusa Dwarf leaf and root explants. Result: Plant seedlings showed decrease in morphological characteristics like plant height, root and shoot length in response to increasing concentrations of heavy metal stress. Similarly carbohydrate content decreased in both leaves and roots while chlorophyll pigments (a+b) increased in leaf explants. Proline and polyphenolic compounds showed an increase in stressed plants compared to control. Conclusions: Plants undertake many adaptive mechanisms for their survival under metal stress which includes morphological as well as biochemical characters. Proline and polyphenolic compounds indicate the presence of excellent antioxidative ingredients to protect the induced by free radicals. Plant protein profiling supports the effect of heavy metal stress in papaya.